Electronic excitation of furfural as probed by high-resolution vacuum ultraviolet spectroscopy, electron energy loss spectroscopy, and ab initio calculations - Silva, F. Ferreira da (2015)
F.F.S. and P.L.V. acknowledge the Portuguese Foundation for Science and Technology (FCT-MEC) through Grant Nos. SFRH/BPD/68979/2010 and SFRH/BSAB/105792/2014, respectively, the research Grant Nos. PTDC/FIS-ATO/1832/2012 and UID/FIS/00068/2013. P.L.V. also acknowledges his Visiting Research Fellow position at Flinders University, Adelaide, South Australia. The Patrimoine of the University of Liege, the Fonds National de la Recherche Scientifique, and the Fonds de la Recherche Fondamentale Collective of Belgium have also supported this research. E.L. and R.F.C.N. thank CNPq (Brazil) and the Science Without Borders Programme for opportunities to study abroad. The authors wish to acknowledge the beam time at the ISA synchrotron at Aarhus University, Denmark. The research leading to these results has received funding from the European Community's Seventh Framework Programme (Grant No. FP7/2007-2013) CALIPSO under Grant Agreement No. 312284. D.B.J. thanks the Australian Research Council for financial support provided through a Discovery Early Career Research Award. M.J.B. also thanks the Australian Research Council for some financial support, while M.J.B. and M.C.A.L. acknowledge the Brazilian agencies CNPq and FAPEMIG for financial support. F.B. and G.G. acknowledge partial financial support from the Spanish Ministry MINECO (Project No. FIS2012-31230) and the EU COST Action No. CM1301 (CELINA). Finally, R.F.C., M.T.do N.V., M.H.F.B., and M.A.P.L. acknowledge support from the Brazilian agency CNPq.